Ultrastructural aspects of the biogenesis of peroxisomes in rat liver - Fahimi, H. Dariush; Baumgart-Vogt, Eveline; Völkl, Alfred (Biochimie, 1993)
A model summarizing our current concepts on the ultrastructural basis of the biogenesis of peroxisomes is presented. Accordingly, the initial stage of de novo build-up of peroxisomes is characterized by the formation of myelin-like figures and membranous attachments onto the surface of pre-existing peroxisomes. Such membranous structures may provide the appropriate lipid environment for the incorporation of peroxisomal membrane proteins and subsequently become the preferential sites for import of newly synthesized matrix proteins. After the import the membranous structures develop into small peroxisomes which may remain attached briefly to the larger particles but eventually separate to become new peroxisomes. Whereas some matrix proteins such as catalase are distributed in all newly formed peroxisomes, other ones like urate oxidase and d-amino acid oxidase are compartmentalized only in some of them, giving rise to heterogeneity of peroxisomes.